Effect of the addition of poultry by-product meal on the zootechnical performance of Nile tilapia fingerlings - Lima, Misleni Ricarte de; Ludke, Maria do Carmo Mohaupt Marques; Santos, Elton Lima; Nunes, César Antunes Rocha; Oliveira, Cláudio José Parro de (Revista de Ciências Agroveterinárias, 2022)
This study has aimed to assess the inclusion of poultry by-product meal in the diets of Nile tilapia fingerlings on heterogeneous growth and zootechnical performance. We used 144 animals with a mean initial weight of 1.3 ± 0.02 g distributed in 24 polyethylene aquariums with a capacity of 80 L of water, connected to a recirculation system following a completely randomized experimental design with four treatments (0.0, 6.0, 12.0, and 18.0% of poultry by-product meal) and six replications. At the end of the experimental period, the following variables were evaluated: final weight, survival rate, weight gain, heterogeneous growth, average feed intake, feed conversion ratio, protein efficiency ratio, and hepatosomatic and liposomatic index. The treatments have had no effect on the variables analyzed in the performance test. Therefore, up to 18% poultry by-product meal can be included in Nile tilapia fingerling diets.